The Antecedents of Intention to Use Telemedicine - Fitri Kinasih Husnul Khotimah; Idqan Fahmi; Sri Hartono (Journal of Consumer Sciences, 2022)
The Covid-19 pandemic has accelerated the adoption of technology in various sectors, one of which is the healthcare industry. Telemedicine users increased during the Covid-19 pandemic, but only 10% of Indonesia's population. This study aims to analyze the factors influencing the intention to use telemedicine. This research uses a descriptive quantitative method. The sampling technique used non-probability sampling with a voluntary sampling technique. Data analysis applied Structural Equation Modeling using LISREL version 8.8. Data were obtained from 225 respondents in Greater Jakarta and Greater Bandung from January to March 2022, but only 192 were included in the analysis. The results showed that the intention to use telemedicine was directly influenced by attitude (A) and indirectly influenced by interrelated variables such as trust (T), perceived ease of use (PEU), perceived usefulness (PU), information quality (IQ), service quality (SrQ), and system quality (SQ). Implications that telemedicine service providers can apply to increase the use of telemedicine are to create the best experience, user friendly, provide complete information, and increase the reliability of information systems.